Psychosocial Therapies for Chronic Headache - J Gordon Millichap (Pediatric Neurology Briefs, 1994)
Psychosocial interventions in the management of recurrent headache disorders are reviewed from Ohio University, Athens, OH, and University of Mississippi Medical Center, Jackson, MS.